Business Models and Sustainability in Nature Tourism: A Systematic Review of the Literature - Sahebalzamani, Samira; Bertella, Giovanna (Sustainability, 2018)
This study explores the business model literature within nature tourism, focuses on its sustainability-related aspects, and adopts some of the results of the literature review by Reinhold et al. The research questions concern how scholars use and operationalize the business model concept in the context of nature tourism, and to what extent sustainability-related aspects are included and discussed. A literature review was conducted including a total of 18 scientific articles from various disciplines. The findings suggest that scientific literature about business models in nature tourism is very limited, both in relation to the number of articles and their content. With regard to the latter, the business model concept is sometimes adopted without any clear definition, sustainability-related aspects—especially those relative to the environmental dimension—are scarcely discussed, the perspective adopted is usually static, and innovation for sustainability is only marginally included. This indicates a clear gap in the literature and a considerable potential for future studies.